The legend : the Bessie Coleman story - Doolittle, Gardner; Walker, Aneva; Raven Productions (Asheville, N.C.); Soundview Media Partners ([Asheville, N.C.] : Gardner Doolittle Films, 2018)
In 1921, a young woman arose from the poverty of the Texas cotton fields. She captured the hearts of the American Black population, teaching them to overcome not only the racial barriers of the time but also the barriers within themselves. She dared to dream, and she challenged them to do so as well. Her name was Bessie Coleman. And, for Bessie Coleman, the sky was the limit... The Legend: The Bessie Coleman Story presents the story of a renowned young woman of vision and courage who, despite the persistent threats of racism, simply refused to compromise herself, her principles, and her race!
Originally released as a motion picture in 2018.
Hosted by Aneva Walker.
Cinematographer, David Gudaitis ; editors, Ryan Butler, Gardner Doolittle ; original music composed by Aneva Walker.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed October 20, 2019)
Keywords: Coleman, Bessie, -- 1892-1926.; African American women air pilots -- Biography; Air pilots -- United States -- Biography; African Americans -- Biography; Women -- Biography; Documentary films; Biographical films; Feature films; Nonfiction films; Internet videos; Streaming video